Debates on Secularisation and Religion in International Politics - OGAR, Tom Eneji; ONAH, Gregory Ajima; OBJANTORO, Enggar; IKHWAN, Afiful (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2023)
Religion’s historical association with violence and extremism has long been a concern in international affairs. The belief that religious differences can spark conflicts has led governments to worry about the potential destabilising influence of religious entities and ideologies in contemporary politics. While the prevailing view emphasises the separation of religion from politics, an increasing number of scholars are challenging the established secularist perspective on religion’s role in international relations. This work contributes to the ongoing reevaluation of religion’s role in politics by addressing three key questions. First, it explores the dominance of secularisation in international relations and the various traditions of secularism that have influenced international political norms. Second, it examines the crisis within the secular orientation of international relations, marked by the diminishing privatisation of religion and the clear division between religion and politics. Finally, it delves into emerging alternative perspectives that challenge secularist hegemony in international relations, shedding light on the distinction between religious and secular processes, institutions, and states and the implications of this differentiation for politics. In pursuit of these questions, the work advances three central arguments. First, it suggests that the Peace of Westphalia did not eliminate religion from politics but rather established a secular discourse rooted in Western Christianity. Second, the work argues that secularism shapes specific conceptions of religion and politics, enforcing a separation between the two. As secularism is inherently influenced by politics, the boundaries it creates between the secular and the religious are subject to change and contestation. Consequently, secularism and religion are not fixed categories, and their relationship to politics remains dynamic and adaptable.